1994
DOI: 10.1136/jmg.31.8.627
|View full text |Cite
|
Sign up to set email alerts
|

Muir-Torre syndrome: a variant of the cancer family syndrome.

Abstract: Muir-Torre syndrome is characterised by the association of sebaceous tumours of the skin with internal malignancy. In many instances there is a strong family history of cancer and the autosomal dominant mode of inheritance, tumour spectrum, and high incidence of synchronous and metachronous tumours show parallels with the cancer family syndrome or Lynch II syndrome. We report a five generation family with at least two persons displaying the Muir-Torre phenotype, while many other family members have had tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Because a subset of patients fulfilling these criteria appeared to have hereditary nonpolyposis colon cancer syndrome (HNPCC), a relation between HNPCC and MTS was first suggested by Lynch in 1981 and later strengthened by linkage analyses [Hall et al, 1994;Lynch et al, 1981]. Subsequently, extensive mutation analyses revealed that the same mutations involved in the pathogenesis of HNPCC were also identified in many patients with MTS Entius et al, 2000;Kruse et al, 1996Kruse et al, , 1998Peris et al, 1997].…”
Section: Introductionmentioning
confidence: 93%
“…Because a subset of patients fulfilling these criteria appeared to have hereditary nonpolyposis colon cancer syndrome (HNPCC), a relation between HNPCC and MTS was first suggested by Lynch in 1981 and later strengthened by linkage analyses [Hall et al, 1994;Lynch et al, 1981]. Subsequently, extensive mutation analyses revealed that the same mutations involved in the pathogenesis of HNPCC were also identified in many patients with MTS Entius et al, 2000;Kruse et al, 1996Kruse et al, , 1998Peris et al, 1997].…”
Section: Introductionmentioning
confidence: 93%
“…4 Eventually, MTS was found to be a variant of HNPCC. 5,6 The pathophysiology involves an autosomally dominant inherited defect in one of the genes encoding the DNA mismatch repair protein (MMRP), resulting in genomic microsatellite instability (MSI). [7][8][9] With a second hit somatic mutation or methylation suppression of the remaining functioning allele, tumors develop.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarialkarzinom (2,6,8,9) Mammakarzinom (2,7,91 Uterustumoren (8) Prostatakrebs (9) Hodentumor (4) Kolontumoren (7,9) Leberkrebs (1,7) Hirntumoren (5) Leukämie (9) Malignes Melanom (3,7) Cefasel forte …”
Section: In Der Krebstherapieunclassified
“…A third group of families has also been identified that resembles Lynch syndrome II families and is known as the Muir-Torre syndrome. This syndrome in cludes in addition to the spectrum of tumours seen in Lynch syndrome II, benign or malignant lesions of the skin such as sebaceous gland tumours, basal cell carcinomas and keratoacanthomas [6,7]. Very recently, a subset of a fourth syndrome has been linked to HNPCC known as Turcot's syndrome.…”
Section: Hereditary Nonpolyposis Colorectal Cancermentioning
confidence: 99%